2017
DOI: 10.1007/s11010-017-3138-2
|View full text |Cite
|
Sign up to set email alerts
|

Ischemic colitis of the colon in streptozotocin-induced diabetic rats

Abstract: This study focuses on two inflammatory diseases, viz., "diabetes mellitus (DM)" that causes serious complications such as retinopathy, nephropathy, and neuropathy, and "ischemic colitis" which is evoked by DM. Ischemic colitis originates from the reduction in mesenteric blood flow to the colon with existence of the occlusive or non-occlusive reasons. Our study objective was to provide early diagnostic approach for ischemic colitis in streptozotocin (STZ)-induced diabetic rats. Sprague-Dawley rats were divided … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…28 In this present investigation, we administered TNBS intrarectally in rats, which was able to exhibit significant similarities with human UC, manifesting cachexia, inflammatory influx, and ulceration. 29 Our study reveals that oral administration of piperine significantly ameliorated TNBS-induced UC by inhibiting several mechanisms such as elevation in oxidative stress (SOD, GSH, MDA, and NO), release of inflammatory mediator (COX-2) and proinflammatory cytokines (TNF-a, ILs, IFN-g, NF-kB, and p-IkBa) as well as apoptosis-related factors (caspase-1). This prevents the destruction of colonic TJ proteins (claudin-1, occluding, and ZO-1), restoring the integrity of the intestinal barrier.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…28 In this present investigation, we administered TNBS intrarectally in rats, which was able to exhibit significant similarities with human UC, manifesting cachexia, inflammatory influx, and ulceration. 29 Our study reveals that oral administration of piperine significantly ameliorated TNBS-induced UC by inhibiting several mechanisms such as elevation in oxidative stress (SOD, GSH, MDA, and NO), release of inflammatory mediator (COX-2) and proinflammatory cytokines (TNF-a, ILs, IFN-g, NF-kB, and p-IkBa) as well as apoptosis-related factors (caspase-1). This prevents the destruction of colonic TJ proteins (claudin-1, occluding, and ZO-1), restoring the integrity of the intestinal barrier.…”
Section: Discussionmentioning
confidence: 66%
“…Furthermore, DAI, macroscopic score, and stool consistency are indirect markers of UC. 29 Rats treated with piperine showed decreased ulcer area and ulcer index, showing piperine's healing potential. Results of the present investigation corroborate with the findings of previous researchers where administration of plant alkaloids such as piperine ameliorates chemical-induced ulcers.…”
Section: Discussionmentioning
confidence: 90%
“…In addition, in some endocrinopathies such as diabetes mellitus, a rat model showed that an increase in calprotectin in serum can indicate complications such as ischemic colitis [ 167 ].…”
Section: Obesity and Endocrine Disorders In Animalsmentioning
confidence: 99%